76 Right mini-thoracotomy surgical Cox-maze (left atrial lesion) vs. catheter ablation using contact force-sensing technology in patients with persistent atrial fibrillation. (8th December 2021) - D'Ambrosio, Gabriele; Raffa, Santi; Romano, Silvio; Alothman, Obaida; Borisov, Georgi; Karam, Issa; Thomas, Kuntze; Geller, J. Christoph
Abstract: Aims: Pulmonary vein isolation (PVI) often is not sufficient in patients (pts) with persistent atrial fibrillation (AF). Substrate modification (SM) by catheter ablation (CA) of low‐voltage zones (LVZ) has yielded favourable results, but those studies were performed before the introduction of contact force (CF) sensing technology. Surgical ablation (SA) studies support the hypothesis that empiric bi-atrial linear ablation (Cox Maze IV procedure) is able to improve success, but there is less data on outcome of patients undergoing left atrial (LA) linear lesions alone. In current guidelines, both CA and SA have Class IIa indication in pts with persistent AF. In this single-centre retrospective study, we analysed the long-term outcomes of CA and SA in pts with persistent AF. Methods and results: In the CA group (Figure 1), pts underwent PVI and additional SM in the presence of LVZ (roof line and supero-septal line) using TactiCath™ or SmartTouch™ ablation catheters aiming at contact values ≥10 g < 20 g and FTI >400 g/s. Ablation was performed in a temperature-controlled fashion with energy of 30 W except at the posterior wall (20–25 W). In the SA group (Figure 2), pts underwent ablation procedure (creation of a pure LA endocardial lesion set consistent with the Cox Maze IV) performed by a right mini-thoracotomy approach using the Atricure™ cryoablation probe, a left atrial appendage (LAA) epicardial exclusion using the Atriclip™ system, and mitral valve repair in the presence of severe mitral valve regurgitation. No right atrial lesions were created. 196 pts were included. 120 pts underwent CA [median age: 65 (58–72) years, median LA volume index (LAVI): 66 (56–75) ml/m 2 ], in pts with LVZs PVI + SM was performed [bidirectional block of lines in 100%]. 76 pts underwent SA [median age: 64 (58–74) years, median LAVI 90 (78–103) ml/m 2 ], in 42 pts a mitral valve repair was performed. At 24 months (figure), 89% and 68% of pts were free of AF in the SA and CA group, respectively, mainly without antiarrhythmic drugs (92% SA group and 89% CA group). Conclusions: In patients with persistent AF, SA performed by a right mini-thoracotomy approach with linear lesions limited to LA leads to excellent 2-year freedom from AF despite significantly larger LAVI compared with the CA group. LAA epicardial exclusion likely contributed to surgical efficacy by eliminating the LAA as trigger/driver.